Application of Artificial Intelligence for managing Diabetes Mellitus patients during the Covid-19 pandemic - Lia Sari; Nurul Darmawulan; Feni Agustina; Nursiswati Nursiswati (Journal of Nursing Care, 2022)
The Covid-19 quarantine policy and mobility restriction were carried out to break coronavirus transmission. These were implemented for several months to affect the quality of life, especially in patients with diabetes mellitus. To overcome this, technology such as applications with artificial intelligence can be used. This literature aims to identify the use of Artificial Intelligence systems in managing diabetes mellitus during pandemics. This review conducted a narrative review method. Articles were searched using databases, such as PubMed, Science Direct, and EBSCO. The keywords were based on the medical subheading (MeSH) term and combined using a boolean operator. Articles were selected using inclusion criteria, namely the year of publication between 2016-2021, articles in English, full text, and open access. The articles that were duplicated and articles that did not fit the research topic were excluded. We found that six articles met the criteria. These discussed four programs, namely diabetes retinopathy screening, blood glucose monitoring, lifestyle management programs, and insulin therapy guidelines. The four programs can be used in the home care services for diabetes mellitus patients during the Covid-19 pandemic